Estimasi Daya Dukung Sumber Daya Air di Pulau Kecil (Studi Kasus Pulau Pari) - Dyah Marganingrum; Yayat Sudrajat (Department of Urban and Regional Planning, Diponegoro University, 2018)
Small islands are often promoted as a tourism destination in spite of the limited fresh water resources availability that they could retain for daily needs. In this context, efforts to provide fresh water resources sustainable in the small island are necessary to support the tourism destination purpose. This study aims to estimate the carrying capacity of the fresh water resources in Pari Island. The estimation method is the ratio between the fresh water availability and its demand by calculating the island size, aquifer thickness, annual rainfall, hydraulic conductivity or soil permeability, and the application of rainwater harvesting technology (RHT). The result shows that the carrying capacity of the fresh water resources without technological intervention in Pari Island is 2.05. Even though this score indicates the safe level, the measure has not taken the water quality into consideration yet. Expectedly, it could be improved by applying the RHT technology but it results in the carrying capacity score of 1.37 and 1.47 (conditionally safe) for the current state and 25-year future prediction respectively. This study recommends the improvements in tourism management by limiting the visitor number in order to support their sustainability for the local livelihood and Pari Island’s ecosystem conservation.